The Adoption of Green Buildings among Contractors in Malaysia - Issanorazura, Idris; Fadzida, Ismail (GBMR, 2023)
Purpose: The proliferation of green buildings is seen as a cost-effective approach to reduce energy use as well as a key construction strategy. However, green building construction has failed to draw the attention of Malaysian contractors because of lack of expertise and awareness as well as uncertainty. Therefore, the purpose of this study is to find the factors that influence the adoption of green building among contractors in Malaysia. Design/methodology/approach: This study uses Technology Acceptance Model (TAM) by focusing on six variables, namely the external factors, perceived ease of use, perceived usefulness, attitude, behavioural intention, and green building, that influence the adoption of green building in construction. The sample of the study includes 138 contractors in Malaysia. The SMART PLS 3 technique is used to evaluate the factors influencing the adoption of green buildings. Findings: The findings show that external factor has a significant effect on the perceived usefulness and perceived ease of use; perceived ease of use has a significant effect on perceived usefulness and attitude; perceived usefulness has a significant effect on attitude and behavioural intention; attitude has a significant effect on behavioural intention; and behavioural intention has a significant impact on green buildings. Research limitations/implications: The implications found involve the requirement of the latest economic and social climate and a tight coordination between the government, local authorities and industry players. The government and local authorities are bound to follow the global moves towards reducing the carbon impact arising out of construction activities, while the industry players are reluctant to follow the effort because of the high starting cost when initiating the green practice. Practical implications: The government and local authority in Malaysia may take an active role as both controller and leading supporter of green building adoption among contractors. By implementing the needed legislation, the technical codes, and the guidelines to manage building environmental performance, the government may be able to respond to the industry’s sustainable trend. In addition, the government may play as the key role in promoting development by identifying and implementing direct financial and non-financial incentive policies.